2005
DOI: 10.1097/01.brs.0000188117.77657.ee
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanism of Ligamentum Flavum Hypertrophy: A Multidisciplinary Investigation Based on Clinical, Biomechanical, Histologic, and Biologic Assessments

Abstract: Fibrosis is the main cause of ligamentum flavum hypertrophy, and fibrosis is caused by the accumulation of mechanical stress with the aging process, especially along the dorsal aspect of the ligamentum flavum. TGF-beta released by the endothelial cells may stimulate fibrosis, especially during the early phase of hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
251
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(279 citation statements)
references
References 18 publications
14
251
2
3
Order By: Relevance
“…Therefore, the vertebral body anteriorly and LF posteriorly must take a major role in balancing the lower lumbar spine and handling the increased spinal load in these people (due to changes in the position of the line of gravity). The outcome is thickening of LF [78][79][80][81][82][83] and modifications of vertebral bodies, i.e., increasing vertebral body surface and decreasing vertebral height. All these alterations may lead in time to degenerative changes of the osseous and nonosseous tissues around the spinal column causing stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the vertebral body anteriorly and LF posteriorly must take a major role in balancing the lower lumbar spine and handling the increased spinal load in these people (due to changes in the position of the line of gravity). The outcome is thickening of LF [78][79][80][81][82][83] and modifications of vertebral bodies, i.e., increasing vertebral body surface and decreasing vertebral height. All these alterations may lead in time to degenerative changes of the osseous and nonosseous tissues around the spinal column causing stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the instantaneous axis of rotation (IAR) of the vertebral body can be useful to assess the kinematics of the lytic spine [19]. A three-dimensional finite element model [5,6,7,10,11,18] (FEM) of the pediatric lumbar spine was developed as described in Part I of this study. This model was used to predict the path of IAR were in flexion/extension, and stresses on the intact and spondylolytic pediatric spines in response to various loading modes.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 During hypertrophy of the ligamentum flavum, there is reduction in the content of elastic fibers and an increase in collagen fibers, calcification, ossification and chondrometaplasia. [4][5][6] Sairyo et al 7,8 have shown a correlation between the hardening of the ligamentum flavum and the degree of fibrosis, resulting in repetitive inflammatory processes due to the mechanical stresses that the ligament suffers during the movements of the spine. Park and collaborators demonstrated that an increase in TGFb (transforming growth factor beta) expression, the protein that controls cell proliferation and acts in the early stages of oncogenesis, is related to hypertrophy of the ligamentum flavum.…”
Section: Introductionmentioning
confidence: 99%